Fast and Sensitive Solution‐Processed Visible‐Blind Perovskite UV Photodetectors. Issue 33 (14th June 2016) - Adinolfi, Valerio; Ouellette, Olivier; Saidaminov, Makhsud I.; Walters, Grant; Abdelhady, Ahmed L.; Bakr, Osman M.; Sargent, Edward H.
Abstract : The first visible‐blind UV photodetector based on MAPbCl3 integrated on a substrate exhibits excellent performance, with responsivities reaching 18 A W −1 below 400 nm and imaging‐compatible response times of 1 ms. This is achieved by using substrate‐integrated single crystals, thus overcoming the severe limitations affecting thin films and offering a new application of efficient, solution‐processed, visible‐transparent perovskite optoelectronics.